2012
DOI: 10.1111/ina.12012
|View full text |Cite
|
Sign up to set email alerts
|

Use of personalized ventilation for improving health, comfort, and performance at high room temperature and humidity

Abstract: In practice, the supply of clean, cool, and less humid air by PV at each workstation will make it possible to raise room temperatures above the upper comfortable limit suggested in the present standards without adversely affecting the occupants' health [Sick Building Syndrome (SBS) symptoms], comfort (thermal and perceived air quality), and performance. This may lead to energy savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 22 publications
4
39
0
1
Order By: Relevance
“…Willem (2006) (19) examined the effect of temperature reduction on stress. According to the results of this study, the de- (22) research increased the sAA, which was consistent with the present study. Lan et al's (2011) study investigated increase of 8°C in temperature (from 22°C to 30°C) on stress, which led to no change in sAA, and was not consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Willem (2006) (19) examined the effect of temperature reduction on stress. According to the results of this study, the de- (22) research increased the sAA, which was consistent with the present study. Lan et al's (2011) study investigated increase of 8°C in temperature (from 22°C to 30°C) on stress, which led to no change in sAA, and was not consistent with the present study.…”
Section: Discussionsupporting
confidence: 92%
“…One recent study investigated the effects of a personalized ventilation system on people's health, comfort, and performance in warm and humid environments (26 and 288C at 70% relative humidity). The system provided increased local air movement and improved perceived air quality (PAQ) and thermal sensation, decreased the intensity of SBS, and improved self-estimated and objectively measured performance (Melikov, Skwarczynski, Kaczmarczyk, & Zabecky, 2013). The authors of another overview of various studies of productivity concluded that robust measures such as occupant control of temperature, operable windows and providing for adaptive thermal comfort could be more effective than increased ventilation or mechanical temperature control (Leyten, Laue, & Kurvers, 2014).…”
Section: Cost Of Comfortmentioning
confidence: 99%
“…16 Personalized ventilation (PV) is one of the solutions that supply clean air close to the breathing zone of the user. 20 Studies show that PV improves occupants' health (reduces sick building syndrome and eye symptoms), perceived air quality, thermal comfort, and work performance, 21,22 and reduces energy consumption. 23,24 A personalized exhaust system with diffusers in the seat headrest has been shown to improve inhaled air quality and reduce exposure to airborne infection in aircraft cabins.…”
mentioning
confidence: 99%